A Modified Particle Swarm Optimization with Dynamic Particles Re-initialization Period - Ratanavilisagul, Chiabwoot; Kruatrachue, Boontee (My University, 2014)
The particle swarm optimization (PSO) is an algorithm that attempts to search for better solution in the solution space by attracting particles to converge toward a particle with the best fitness. PSO is typically troubled with the problems of trapping in local optimum and premature convergence. In order to overcome both problems, we propose an improved PSO algorithm that can re-initialize particles dynamically when swarm traps in local optimum. Moreover, the particle re-initialization period can be adjusted to solve the problem appropriately. The proposed technique is tested on benchmark functions and gives more satisfied search results in comparison with PSOs for the benchmark functions. © Springer International Publishing Switzerland 2014.
Keywords: Multi-start Particles; Mutation operator; Particle Swarm Optimization; Particles Re-initialization